Nerve growth factor in muscle afferent neurons of peripheral artery disease and autonomic function - Lu Qin; Jianhua Li (Neural Regeneration Research, 2021)
In peripheral artery disease patients, the blood supply directed to the lower limbs is reduced. This results in severe limb ischemia and thereby enhances pain sensitivity in lower limbs. The painful perception is induced and exaggerate during walking, and is relieved by rest. This symptom is termed by intermittent claudication. The limb ischemia also amplifies autonomic responses during exercise. In the process of pain and autonomic responses originating exercising muscle, a number of receptors in afferent nerves sense ischemic changes and send signals to the central nervous system leading to autonomic responses. This review integrates recent study results in terms of perspectives including how nerve growth factor affects muscle sensory nerve receptors in peripheral artery disease and thereby alters responses of sympathetic nerve activity and blood pressure to active muscle. For the sensory nerve receptors, we emphasize the role played by transient receptor potential vanilloid type 1, purinergic P2X purinoceptor 3 and acid sensing ion channel subtype 3 in amplified sympathetic nerve activity responses in peripheral artery disease.